An Economic Evaluation of Voriconazole versus Amphotericin B for the Treatment of Invasive Aspergillosis in Canada. Issue 5 (1st October 2004) - Rotstein, Coleman; Laverdière, Michel; Marciniak, Anne; Ali, Farzad
Abstract : BACKGROUND: Invasive aspergillosis (IA) is a serious fungal infection that affects immunocompromised patients. The Global Comparative Aspergillosis study demonstrated that voriconazole, a new broad-spectrum triazole, had better responses and improved survival compared with conventional amphotericin B deoxycholate (CAB) and other licensed antifungal therapy (OLAT) for the treatment of definite or probable aspergillosis. OBJECTIVES: To compare costs and outcomes of voriconazole and CAB for the treatment of definite or probable aspergillosis in Canada. METHODS: A cost-consequence decision tree model was designed to reflect the treatment pathways used in clinical practice when using voriconazole or CAB as primary therapy for IA. Therapy included initial treatment with either voriconazole or CAB and then switched to an OLAT in the event of an inadequate response, severe toxicity or intolerance. The principal data source used was the Global Comparative Aspergillosis study. RESULTS: The total cost of voriconazole when compared with CAB as initial therapy for IA was $38, 319 versus $42, 495 per patient, respectively, representing a 9.8% cost reduction for each patient treated with voriconazole. The higher mean cost in the CAB arm was primarily due to the high proportion of patients (73.7%) who were switched to an OLAT due to severe side effects or an inadequate response. Treating with voriconazole was a dominant strategy. The number of patients that had to be treated with voriconazole instead of CAB to save one additional life was eight. CONCLUSIONS: Voriconazole as primary treatment for IA increased the chances of successful treatment, improved survival and may represent a potential cost saving strategy in Canada.